Impact of patient compliance with inhaler therapy on chronic obstructive pulmonary disease severity: a rural tertiary care perspective - Nandakishore K. S.; Preethiraj Ballal; Anirudha Katipalla; Shruthi Rai P.; Supreetha T.; Dixith T.; Sanjay Srinivas; Shree Dhanusha; Pramod Pujar; Sushmitha Sudeesh; Vignesh T. M. (The Egyptian Journal of Internal Medicine)
Abstract Background Inhaled medications have been the cornerstone of treatment for the exacerbations as well as stable chronic obstructive pulmonary disease (COPD) which is one of the leading cause of deaths in the recent times. Inadequate knowledge on handling of inhalers leads to noncompliance which in turn results in increased hospital visits limelighting the negative impact on the morbidity status. The aim of our study was to assess the compliance of inhalers and to correlate the level of compliance to the morbidity of COPD as assessed by number of hospital visits. Methods In our cross-sectional observational study conducted in the rural medical college hospital in Dakshina Kannada of Karnataka, 69 subjects with COPD were evaluated for the compliance of inhaler usage, and the morbidity related to the disease was assessed with number of hospital visits in the past 6 months. Appropriate statistical analysis was used in evaluation. Results Out of 69 patients, 24 patients visited the health care facility at least 3 times or more. Of these 24 patients, 20 (83.33%) of them were not compliant with inhalers. Among the 45 patients who visited the health care facility less than 2 times, 28 (62.22%) patients were compliant with inhalers. This relationship was found to be statistically significant proving that the higher the number of visits, the lesser the compliance and vice versa. Conclusions Our study highlights the importance of patient education about compliance to inhalers which is an economical and effective modality which has significant impact on reduction of exacerbations and morbidity.